Validity and reliability of short‐term heart‐rate variability from disposable electrocardiography leads. Issue 1 (8th December 2022) - Okwose, Nduka C.; Russell, Sophie L.; Rahman, Mushidur; Steward, Charles J.; Harwood, Amy E.; McGregor, Gordon; Ninkovic, Srdjan; Maddock, Helen; Banerjee, Prithwish; Jakovljevic, Djordje G.
Abstract: Background and Aims: Single‐use electrocardiography (ECG) leads have been developed to reduce healthcare‐associated infection. This study compared the validity and reliability of short‐term heart rate variability (HRV) obtained from single‐use disposable ECG leads. Methods: Thirty healthy subjects (33 ± 10 years; 9 females) underwent 5‐min resting HRV assessments using disposable (single use) ECG cable and wire system (Kendall DL™ Cardinal Health) and a standard, reusable ECG leads (CardioExpress, Spacelabs Healthcare). Results: Intraclass correlation coefficient (ICC) with 95% confidence interval (CI) between disposable and reusable ECG leads was for the time domain [R‐R interval (ms); 0.99 (0.91, 1.00)], the root mean square of successive normal R‐R interval differences (RMSSD) (ms); 0.91 (0.76, 0.96), the SD of normal‐to‐normal R‐R intervals (SDNN) (ms); 0.91 (0.68, 0.97) and frequency domain [low‐frequency (LF) normalized units (nu); 0.90 (0.79, 0.95), high frequency (HF) nu; 0.91 (0.80, 0.96), LF power (ms 2 ); 0.89 (0.62, 0.96), HF power (ms 2 ); 0.90 (0.72, 0.96)] variables. The mean difference and upper and lower limits of agreement between disposable and reusable leads for time‐ and frequency‐domain variables were acceptable. Analysis of repeated measures using disposable leads demonstrated excellent reproducibility (ICC 95% CI) for R‐R interval (ms); 0.93 (0.85, 0.97), RMSSD (ms); 0.93 (0.85, 0.97), SDNN (ms); 0.88 (0.75, 0.95), LF power (ms 2 ); 0.87 (0.72, 0.94), and HF power (ms 2 ); 0.88 (0.73, 0.94) with coefficient of variation ranging from 2.2% to 5% ( p > 0.37 for all variables). Conclusion: Single‐use Kendall DL™ ECG leads demonstrate a valid and reproducible tool for the assessment of HRV.